How introduction of automated insulin delivery systems may influence psychosocial outcomes in adults with type 1 diabetes: Findings from the first investigation with the Omnipod® 5 System. (August 2022) - Polonsky, William H.; Hood, Korey K.; Levy, Carol J.; MacLeish, Sarah A.; Hirsch, Irl B.; Brown, Sue A.; Bode, Bruce W.; Carlson, Anders L.; Shah, Viral N.; Weinstock, Ruth S.; Bhargava, Anuj; Jones, Thomas C.; et al.
Highlights: Adults with T1D used an investigational tubeless Omnipod 5 AID system for 3 months. Participants saw improvements in diabetes-related psychosocial outcomes with AID. Even with positive outcomes with prior therapy, improvements were still observed. Improvements were not consistently associated with any baseline characteristics. Positive psychosocial outcomes with AID systems support adoption and long-term use. Abstract: Aims: To evaluate psychosocial outcomes for adults with type 1 diabetes (T1D) using the tubeless Omnipod® 5 Automated Insulin Delivery (AID) System. Methods: A single-arm, multicenter (across the United States), prospective safety and efficacy study of the tubeless AID system included 115 adults with T1D. Participants aged 18–70 years completed questionnaires assessing psychosocial outcomes – diabetes distress (T1-DDS), hypoglycemic confidence (HCS), well-being (WHO-5), sleep quality (PSQI), insulin delivery satisfaction (IDSS), diabetes treatment satisfaction (DTSQ), and system usability (SUS) – before and after 3 months of AID use. Associations among participant characteristics, psychosocial measures and glycemic outcomes were evaluated using linear regression analyses. Results: Adults using the tubeless AID system demonstrated improvements in diabetes-specific psychosocial measures, including diabetes distress, hypoglycemic confidence, insulin delivery satisfaction, diabetes treatment satisfaction, and system usability after 3 months (all P < 0.001). No changes in general well-being or sleep quality were observed. The psychosocial outcomes assessed were not consistently associated with baseline participant characteristics (i.e., age, sex, diabetes duration, glycemic outcomes including percent time in range 70–180 mg/dL, percent time below range < 70 mg/dL, hemoglobin A1c, or insulin regimen). Conclusions: Use of the Omnipod 5 AID system was associated with significant improvements in diabetes-related psychosocial outcomes for adults with T1D. Clinical Trials Registration Number: NCT04196140.